(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
In order to evaluate the allelopathic effect of Sorghum halepense extracts on germination and initial growth of six pea (Pisum sativum subsp. sativum, Pisum sativum subsp. arvense) cultivars and to identify tolerant cultivars, a laboratory experiment was conducted. The studied cultivars revealed different levels of susceptibility to allelopathic impact of root and aboveground biomass extracts of S. halepense. Root growth parameters (length and weight) of the pea cultivars exhibited greater susceptibility to weed extracts than stem parameters. The inhibitory effects of the extracts on germ length of P. sativum ranged from 1.4% (cultivar Mir) to 45.0% (Kamerton), on germ weight – from 3.5% (Pleven 4) to 42.9% (K-80), and on seed germination – from 11.8% (Mir) to 31.3% (K-80). Total inhibitory effect, i.e. the impact of S. halepense extracts on all studied parameters of P. sativum, revealed that the cultivars Mir and Pleven 4 were the most tolerant. Growing such cultivars may reduce weed damage. Low tolerance was manifested by the cultivar K-80, while Modus, Glyans and Kamerton ranked intermediate. The cultivars with large-size seeds or lower grain protein content were more affected by the depressing effect of S. halepense extracts.